Tracking production strategies: Identifying compositional methods in electroacoustic music. Issue 3 (1st December 2013) - Moore, Adrian; Moore, Dave; Pearse, Stephen; Stansbie, Adam
In recent years, electroacoustic theorists have drawn attention to the experiences and interpretations of listeners; well-known examples include the writings of Stéphane Roy, Luke Windsor, Christiane Ten Hoopen and Denis Smalley. During the same period, relatively little has been said about the methods and techniques employed by composers during the creation of their works. This article starts by considering some of the reasons why methods have been overlooked within the existing body of literature. It goes on to discuss the existing software tool developed at the University of Sheffield, and explains how this software documents the process chain and affords an interaction with the compositional process. The software is then contextualized within a proposed research project, which aims to further develop the software tools, and deliver a series of complete compositional traces by a number of composers, offering these for compilation and comparison. It finishes by proposing ways in which compositional methods might be identified and analysed.